Design research : investigation for successful creative solutions - Leonard, Neil.; Ambrose, Gavin (Lausanne, Switzerland : AVA Academia, 2012)
Design research will guide the reader through the early stages of a design project, identifying appropriate research techniques and enabling innovative solutions to be found.
The basics of research : Why research? ; Getting started ; Primary, secondary and tertiary ; Key terminology ; Studio interview : Emily Hale ; Activity : Approaching research -- Understanding context : Audience and social contexts ; Design contexts ; Theoretical underpinning ; Studio interview : Andrew Hussey ; Activity : Convention -- Planning your work : the brief ; Audience ; Sources and credibility ; Recording and documenting ; Studio interview : Brian Rea ; Activity : Audience -- Conduction research : Audience research ; Market research ; Field-based research ; Process-based research ; Studio interview ; Jane Trustram ; Activity : Product and customer -- Using your findings : Understanding your findings ; Responding to your findings ; Studio interview : Underware ; Activity : Classification -- Presenting your findings : Presenting research ; Completing the job ; Studio interview : Tanner Christensen ; Activity : Presenting statistics -- Conclusion.
Includes bibliographical references and index.
Tertiary/Undergraduate, Postgraduate.
Keywords: Graphic arts -- Technique; Design -- Research; Commercial art